SISTEM INFORMASI GEOGRAFIS JARINGAN JALAN KABUPATEN SIAK PROPINSI RIAU - Wartika Wartika; Mahfud Abdul Ghoni (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2011)
Siak Regency is one of the districts included in the area of Riau Province. As a growing district, the existence of roads is very important to support programs Siak District Government. In managing the data path, Siak District Government is still using the archive documents the survey and its management is still manual. Therefore, in this study will discuss the design of Geographic Information Systems of Siak Regency Road Network to facilitate the data management path. In addition to designing geographic information systems, another goal that will be done is to implement and test the Geographic Information System of Siak Regency Road Network which has been designed previously. Geographic Information Systems in the design of this road network, data collection methods used were observation and interviews, the method of approach used is a structured approach method, the method of system development using the waterfall model. Tools for analysis and design includes flowmap, context diagrams, data flow diagram of a relation table, entity relationship diagrams and data dictionary. The software used in the design of Geographic Information System of Siak Regency Road Network is a Microsoft Visual Basic.net as an interface, Microsoft Office Access as the database and MapInfo MapX 5.0 as a data processing map. Results from this study is a Geographical Information System of Siak Regency Road Network is expected to help performance Siak District Government to manage the data path. It also can be used to compile reports relating to the road network data.